Understanding Consumer Purchase Intention towards Biodegradable Footwear: A Study - Kishore Kumar, P.; Anand, Byram (Indian Journal of Marketing, 2013)
Business processes are redesigning themselves into green business processes to sustain themselves in the modern business world. Pollution and climate change are the major factors which are influencing the organizations to launch biodegradable products which are environment friendly. The companies in the global footwear industry are launching biodegradable footwear products, and the present paper discusses consumer behavior with reference to the purchase of biodegradable footwear. A questionnaire based survey was conducted in Hyderabad, and the sample size for the study was 120 respondents. It was found that there is lot of consumer awareness about green products, but purchase intention of the consumers influenced them significantly with reference to the purchase of biodegradable footwear. Hence, it is concluded that organizations should develop commercials/advertisements to increase the purchase intention of biodegradable footwear among the consumers. In addition, online marketing tools should be used to market biodegradable footwear.